2018
DOI: 10.1096/fj.201800151rr
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of microRNA‐351 exerts protective effects during sepsis by ameliorating skeletal muscle wasting through the Tead‐4‐mediated blockade of the Hippo signaling pathway

Abstract: Sepsis-induced skeletal muscle wasting may lead to various severe clinical consequences. Understanding molecular mechanisms of the regulation of the loss of skeletal muscle mass in septic patients remains a significant clinical challenge. The current study was conducted to establish septic mice models to explore the relationship between microRNA (miR)-351 and the transcription element apical (TEA) domain transcription factor (Tead)-4 gene and to investigate its effects on the skeletal muscle through mediating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Another study also demonstrated the interaction between miR-140 -5p and the WNT/␤-catenin signaling pathway, suggesting that miR-140 -5p could inactivate the WNT/␤-catenin signaling pathway by binding to WNT1 gene, thereby suppressing the hypoxic-ischemic brain damage (7). As a previous study reported by Zhang et al, the upregulation of miR-351 could attenuate acute sepsis in mice by reducing the degradation of skeletal muscle protein and skeletal muscle atrophy by regulation of the target gene Tead-4 via inactivation of the Hippo signaling pathway (32). For the present study, apart from the effect of miR on skeletal muscle atrophy, production of Tyr and 3-MH, Bcl-2 expression, and skeletal muscle apoptosis, we further explored the effects of miR-140 on muscle fiber cross-sectional areas and lactic acid production to thoroughly confirm the inhibitory role of miR-140 in endotoxin-treated mice.…”
Section: Discussionmentioning
confidence: 78%
“…Another study also demonstrated the interaction between miR-140 -5p and the WNT/␤-catenin signaling pathway, suggesting that miR-140 -5p could inactivate the WNT/␤-catenin signaling pathway by binding to WNT1 gene, thereby suppressing the hypoxic-ischemic brain damage (7). As a previous study reported by Zhang et al, the upregulation of miR-351 could attenuate acute sepsis in mice by reducing the degradation of skeletal muscle protein and skeletal muscle atrophy by regulation of the target gene Tead-4 via inactivation of the Hippo signaling pathway (32). For the present study, apart from the effect of miR on skeletal muscle atrophy, production of Tyr and 3-MH, Bcl-2 expression, and skeletal muscle apoptosis, we further explored the effects of miR-140 on muscle fiber cross-sectional areas and lactic acid production to thoroughly confirm the inhibitory role of miR-140 in endotoxin-treated mice.…”
Section: Discussionmentioning
confidence: 78%
“…The remaining 80 mice were used to establish sepsis models, and the success rate was 67.5%. The mouse model of sepsis was established as previously reported 31 . In short, the mice were anesthetized with 3% sodium pentobarbital (no.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, ferroptosis activation has been reported to induce acute kidney failure and early death in mice caused by the disruption of GPX4 26 . In addition, a recent study demonstrated that ferroptosis is involved in RM associated kidney damage in vivo and in vitro 32 . RM causes the release of MB and other muscle cell components to the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…RM causes the release of MB and other muscle cell components to the bloodstream. MB is freely filtered by glomeruli and reabsorbed by proximal tubules, promoting ferroptosis‐mediated cell death, thus leading to AKI, the treatment of Fer‐1 strongly inhibits the severity of AKI via decreasing the MB‐derived iron accumulation and lipid peroxidation 32 . This is consistent with the results in current study, RM following the EHS could induce remarkable AKI and the severity of AKI induced by the RM after EHS were strongly ameliorated by the Fer‐1 administration in vivo .…”
Section: Discussionmentioning
confidence: 99%